2013
DOI: 10.1063/1.4826527
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion of Ni-Al multilayers: A continuum and molecular dynamics study

Abstract: Molecular dynamics simulation of Al/Ni multilayered foils reveals a range of different reaction pathways depending on the temperature of the reaction. At the highest temperatures Fickian interdiffusion dominates the intermixing process. At intermediate temperatures Ni dissolution into the Al liquid becomes the dominant mechanism for intermixing prior to formation of the B2 intermetallic phase. At lower temperatures the B2 intermetallic forms early in the reaction process precluding both of these mechanisms. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
(66 reference statements)
7
21
0
Order By: Relevance
“…Instead, a slow rate based on diffusion through a solid state product layer should be considered in the dark zones between transverse bands, and a fast rate based on direct dissolution of the refractory element into the liquid state of the fusible element should be considered in the transverse reaction bands themselves. This agrees with recent molecular dynamics simulations performed by Alawieh et al 31 and by Xu et al 32 In their work, Alawieh et al described the temperature-dependent mass diffusivity of Ni/Al nanolaminates, a system similar to the Co/Al laminates studied here. It was shown that there is a significant and discontinuous increase in diffusivity at temperatures below the melting point of Al.…”
Section: Partial Reaction Ahead Of Stalled Reaction Frontssupporting
confidence: 92%
“…Instead, a slow rate based on diffusion through a solid state product layer should be considered in the dark zones between transverse bands, and a fast rate based on direct dissolution of the refractory element into the liquid state of the fusible element should be considered in the transverse reaction bands themselves. This agrees with recent molecular dynamics simulations performed by Alawieh et al 31 and by Xu et al 32 In their work, Alawieh et al described the temperature-dependent mass diffusivity of Ni/Al nanolaminates, a system similar to the Co/Al laminates studied here. It was shown that there is a significant and discontinuous increase in diffusivity at temperatures below the melting point of Al.…”
Section: Partial Reaction Ahead Of Stalled Reaction Frontssupporting
confidence: 92%
“…Molecular dynamics simulations have contributed to studies of reactive multilayers [179][180][181][182][183]. In particular, MD has been vital for investigating the diffusivity of reactants at high temperatures, information that is not readily available through experiments.…”
Section: Model Descriptions Of Steady Propagating Reactionsmentioning
confidence: 99%
“…Artificially maintaining a constant temperature during reaction in atomistic simulations has resulted in the formation of the B2 (NiAl intermetallic) [25][26][27]. The nucleation of B2, which followed the amorphization of the Al-rich side, was seen to adversely affect the effective diffusion rates [27]. However, the isothermal nature of these simulations do not allow for the study of the interplay between fast reaction kinetics and the formation of the intermetallic phases.…”
Section: Introductionmentioning
confidence: 96%
“…All prior adiabatic simulations failed to observe the formation of intermetallics during reaction. Artificially maintaining a constant temperature during reaction in atomistic simulations has resulted in the formation of the B2 (NiAl intermetallic) [25][26][27]. The nucleation of B2, which followed the amorphization of the Al-rich side, was seen to adversely affect the effective diffusion rates [27].…”
Section: Introductionmentioning
confidence: 97%